PENINGKATAN KUALITAS PEMBELAJARAN DI SMK ISLAM DARUT TAUHID TELUK PAKEDAI: BERBASIS STATISTICAL PROCESS CONTROL - Murni Murni; Abdul Wahab (Jurnal Manajemen Pendidikan, 2026)
Vocational High Schools (SMK) are expected to possess not only academic competence but also professional skills, character, and work readiness that meet industry demands. However, challenges in managing learning quality remain. This study analyzes the implementation of Statistical Process Control (SPC) in improving learning quality at SMK Islam Darut Tauhid Teluk Pakedai. A mixed-method approach with a case study design was employed. Data was collected through observations, interviews, and documentation of academic records. SPC tools used in this study included check sheets, control charts, Pareto diagrams, histograms, and fishbone diagrams. The findings indicate that SPC is relevant and effective in supporting learning quality improvement, strengthening academic culture, and enhancing teacher professionalism. Control charts assist in identifying variations in learning processes and deviations in academic data. Learning quality problems are mainly caused by low student motivation, variations in teaching methods, and weak monitoring systems. Human resources, instructional methods, learning media, and environmental factors contribute to inconsistencies in learning quality. Therefore, effective SPC implementation requires teachers’ statistical competence, integrated educational management information systems, and a strong organizational commitment to continuous quality improvement.